2019
DOI: 10.1016/j.neurobiolaging.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in GABA following a tDCS-language intervention for primary progressive aphasia

Abstract: Transcranial Direct Current Stimulation (tDCS) has shown efficacy in augmenting the effects of language therapy in Primary Progressive Aphasia (PPA). The mechanism of action of tDCS is not understood but preliminary work in healthy adults suggests it modulates GABA levels to create an environment optimal for learning. It is unknown if this proposed mechanism translates to aging or neurodegenerative conditions. This study tested the hypothesis that tDCS reduces GABA at the stimulated tissue in primary progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
0
38
1
Order By: Relevance
“…The prolonged and promising changes in both cortical excitability and promising changes in behavioral outcomes combined with its simple application and low cost makes tDCS an attractive as a possible therapeutic tool for a range of clinical conditions [5]. For example, tDCS has been suggested to improve symptoms and/or assist in rehabilitation for many neurological disorders with minimal side effects [6], including migraine [7], stroke [8], Parkinson's disease [9], pain disorders [10] and neurodegenerative disorders [11], as well as psychiatric disorders including depression [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged and promising changes in both cortical excitability and promising changes in behavioral outcomes combined with its simple application and low cost makes tDCS an attractive as a possible therapeutic tool for a range of clinical conditions [5]. For example, tDCS has been suggested to improve symptoms and/or assist in rehabilitation for many neurological disorders with minimal side effects [6], including migraine [7], stroke [8], Parkinson's disease [9], pain disorders [10] and neurodegenerative disorders [11], as well as psychiatric disorders including depression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive stimulation is an expanding area of research with investigations into the use of modalities similar to tDCS being investigated as a therapy for a range of disorders including migraine, pain and stroke (6,7,9,11,12,18,67). While these studies have suggested that noninvasive brain stimulation can improve outcomes, there is little analysis into the underlying physiological changes behind these responses are not well understood, particularly in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Adult literature using healthy controls suggests acute decrease in GABA local to the tDCS target (4,25,26,48). Similarly, participants with a neurodegenerative condition who followed a protocol of 15 a-tDCS sessions also showed decreased GABA in the tissue targeted with a-tDCS (11).…”
Section: Post-intervention Changes In Gaba and Glxmentioning
confidence: 92%
See 2 more Smart Citations